The Investigation of the Iranian Athletics Sport Wears Comparing with European Countries Based on the Design, Form and Applicability - Pakbin, Sedigheh (Journal of History Culture and Art Research, 2017)
Each kind of sport needs a special sport wear in order to provide an appropriate condition for sport activities. There are different valid sport brands in European countries that represent fashionable designs and models. The sport wears indicate the nature of the manufacturer country. In Iran, officials must pay full attention to the sport wears of athletics in both international and national plays. In this regard, the aim of the present study is identifying the sport wears in Iran as well as comparing with European models on the basis of design, form and application. From the viewpoint of view, the present research is applied one and also it is descriptive. The statistical community of the present research is all the producers of sport wears in Tehran. Excel software was also used in this study in order to analyze the data. The results indicate that the form and material of the sport wear is a significance issue among European brands. It is also observed that the factories of sport wear try to enhance their performances. Meanwhile, the most Iranian producers try to copying these models from the foreign brands. They don’t like to produce new and domestic designs. According to the present study, it was indicated that Iranian producers seldom pay attention to the application of these cloths.